Repetitive auditory stimulation at a critical prenatal period modulates the postnatal functional development of the auditory as well as visual system in chicks (Gallus domesticus). Issue 9 (2nd July 2013) - Roy, Saborni; Nag, Tapas C.; Upadhyay, Ashish Datt; Mathur, Rashmi; Jain, Suman
ABSTRACT The extrinsic sensory stimulation plays a crucial role in the formation and integration of sensory modalities during development. Postnatal behavior is thereby influenced by the type and timing of presentation of prenatal sensory stimuli. In this study, fertilized eggs of white Leghorn chickens during incubation were exposed to either species‐specific calls or no sound. To find the prenatal critical period when auditory stimulation can modulate visual system development, the former group was divided into three subgroups: in subgroup A (SGA), the stimulus was provided during embryonic day (E)10 to E16, in SGB E17‐ hatching, and in SGC E10‐hatching. The auditory and visual perceptual learning was recorded at posthatch day (PH) 1–3, whereas synaptic plasticity (evident from synaptophysin and PSD‐95 expression), was observed at E19, E20, and PH 1–3. An increased number of responders were observed in both auditory and visual preference tests at PH 1 following stimulation. Although a decrease in latency of entry and an increase in total time spent were observed in all stimulated groups, it was most significant in SGC in auditory preference and in SGB and SGC in visual preference test. The auditory cortex of SGC and visual Wulst of SGB and SGC revealed higher expression of synaptic proteins, compared to control and SGA. A significant inter‐hemispheric and gender‐based difference in expression was also found in all groups. These results indicate facilitation of postnatal behaviour and synaptogenesis in both auditory and visual systems following prenatal repetitive auditory stimulation, only when given during prenatal critical period of development. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 73: 688–701, 2013